FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Miedya Wulansari, 13.05.52.0219; Nurhayati, Ida (Students Journal of Accounting and Banking, 2017)
This study examines the effect of inventory variability, firm size, inventory intensity, ownership structure and variability of cost of goods sold, to the selection of inventory accounting methods. This research is conducted at Indonesia Stock Exchange by using unit of analysis of manufacturing company which have go public. Sampling method in this research use purposive sampling with research period year 2013 until 2015. The relationship and or influence between independent variable with dependent variable is explained by using logistic regression analysis method. The results of the research are as follows: firm size, variability of cost of goods sold and ownership structure have a significant effect on the choice of inventory accounting method, while inventory intensity, inventory variability have no significant effect on the choice of inventory accounting method.Keywords: Inventory Variability, Inventory Size, Intensity of Inventory, Managerial Ownership Structure, Variability of Cost of Goods Sold, Selection Inventory Accounting Method